2020
DOI: 10.33736/bjrst.2475.2020
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics Determination in the Rivers with Different Urbanisation Variances: A Case Study in Kuching City, Sarawak, Malaysia

Abstract: The presence of microplastics in aquatic systems is mainly due to the anthropogenic activities such as domestic waste dumping. Undeniably, rivers either in urban or suburban areas are always a waste dumpling sites from the surrounding residences. Thus, the purpose of this study was to determine the relationship between microplastic abundance and different degree of urbanization across Kuching in Sarawak. Three sampling locations with different degrees of urbanisation had been studied across Kuching. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A study conducted by Di and Wang [19] in Three Gorges Reservoir, China showed that the average of microplastics tend to be highest in urban areas, followed by suburban and rural areas. These significant spatial variations between different areas can also be observed in Taihu Lake, China [20], lakes in Wuhan City, China [21], rivers in Japan [22] and rivers in Kuching, Malaysia [23]. Geographic and topographic properties of the waterbody also influence the microplastics abundance.…”
Section: Occurrence and Size Distribution Of Microplasticsmentioning
confidence: 93%
See 1 more Smart Citation
“…A study conducted by Di and Wang [19] in Three Gorges Reservoir, China showed that the average of microplastics tend to be highest in urban areas, followed by suburban and rural areas. These significant spatial variations between different areas can also be observed in Taihu Lake, China [20], lakes in Wuhan City, China [21], rivers in Japan [22] and rivers in Kuching, Malaysia [23]. Geographic and topographic properties of the waterbody also influence the microplastics abundance.…”
Section: Occurrence and Size Distribution Of Microplasticsmentioning
confidence: 93%
“…Microbeads are mainly incorporated with personal care products like facial scrub and soap. However, due to their tiny sizes, microbeads were easily escaped the wastewater treatment plants and thus end up in the river or lake, as shown in the study by Johnson et al [23] in Kuap, Maong and Sarawak Rivers, Malaysia. Microbeads were made from several plastic polymers such as PE, PP, PET, PMMA and PA.…”
Section: Morphological Characteristics and Sources Of Microplasticsmentioning
confidence: 99%
“…Kuap River and Maong River contain the second-and third-highest levels of microplastic, respectively, due to the presence of only residential areas and human habitats. The majority of plastic wastes from residential or human living areas have been disposed of in the garbage or recycling bins, and then transported to an integrated waste management facility [15]. The gray water waste containing microplastics has been released directly into the river without treatment or filtration.…”
Section: Overview Of Microplastics In Aquatic Animalsmentioning
confidence: 99%